RENCANA ANGGARAN BIAYA DAN TIME SCHEDULE PEMBANGUNAN GEDUNG 5 LANTAI REKTORAT UNIVERSITAS HASYIM ASY’ARI - Tah Sin Hal; Titin Sundari (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Construction project activity planning is very important because activity planning or scheduling is a key factor for the project to run smoothly and the project being implemented can be completed within the optimal time. In planning the implementation of this project work, the final results are in the form of time and costs of implementation in accordance with the planned method. In calculating the budget plan for the construction of a 5-story Rectorate Building at Hasyim Asy'ari University with a building area of ​​± 1230 m², accuracy is required in calculating the volume of work. Unit prices for work and wages also require complete drawing references. For work without available analysis, it is necessary to conduct your own analysis calculations and price surveys to obtain appropriate estimates, such as for mobilization and demobilization work items. Based on these calculations, the total cost required is Rp24,509,796,848.92. The time schedule, which is a time allocation plan to complete all work items in the project, is displayed in the form of an S-curve. From the preparation of this time schedule, it is estimated that the construction project of the 5-story Rectorate Building at Hasyim Asy'ari University will require 234 days to complete..